Radônio como indicador de contaminação de solos por hidrocarbonetos - Barbosa, Eder Queiroz [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Previous studies show that in areas contaminated by fuel spill (NAPL- non-aqueous phase liquids), from operational activities, transport and storage, it was possible to observe a significant decrease of ²²²Rn (radon) gas concentration in the soil, even a non-uniform distribution of this gas in top soil, even with a geological situation was practically homogeneous. These anomalies may be associated with the preference partitioning of radon in NAPLs. This work consists of applying ²²²Rn as an indicator for locating subsurface contamination by NAPLs in an area of the city of Rio Claro (SP) where, according to the “Survey of Contaminated and Rehabilitated Areas in the State of São Paulo (Environmental Sanitation and Technology Company - CETESB), there was, in the year 2007, groundwater contamination from leaks of liquid fuels. The challenges of this research are: Promulgate the use of a new tool with greater efficiency in obtaining results, in addition to generate less impact in half and have less expenditure; disseminate scientific culture promoting greater integration of C&T (culture & technology) between universities and businesses. The emanometric technique to estimate the location, number and interfacial area of NAPL in saturated and non-saturated zone, has the advantage of locating and determining plumes of free phase even when the amount of VOC's (Volatile Organic Compounds) that reaches the surface is low or non-existent. In addition, the measurement techniques ²²²Rn are quite developed. The results obtained show that, similar to the other studies, the 222Rn soil gas presents an anomalous behavior in the area bounded by NAPL plume, being possible to note a significant deficit in the concentration of the gas in spots where the saturation by NAPLs is still critical. Therefore it is concluded that this tool is really promising, but we must be careful to evaluate the initial conditions of the area, as well as the type of...

Estudos anteriores demonstram que em áreas contaminadas por derramamento de combustíveis (NAPL – fase liquída não aquosa), provenientes de atividades de explotação, transporte e armazenamento, foi possível observar um decréscimo significativo da concentração de gás ²²²Rn (radônio) no solo, observando-se ainda uma distribuição não uniforme deste gás em solo superior, mesmo havendo uma situação geológica praticamente homogênea. Estas anomalias podem ser associadas com o particionamento preferencial do radônio em NAPLs. O trabalho consiste na aplicação do ²²²Rn como indicador para a localização de contaminação subsuperficial por NAPLs em uma área do município de Rio Claro (SP) onde , segundo o levantamento de “Áreas Contaminadas e Reabilitadas no Estado de São Paulo” (Companhia de Tecnologia de Saneamento Ambiental - CETESB), houve, no ano de 2007, a constatação de contaminação das águas subterrâneas provenientes do vazamento de combustíveis líquidos. Os desafios desta pesquisa são: Promulgar a utilização de uma nova ferramenta com maior eficiência na obtenção de resultados, além de gerar menos impactos ao meio e ter menor dispêndio; disseminar a cultura científica promovendo maior integração da C&T (cultura & tecnologia) entre universidades e empresas. A técnica emanométrica para estimar a localização, quantidade e área interfacial de NAPL na zona não-saturada e saturada possui a vantagem de localizar e determinar plumas de fase livre mesmo quando a quantidade de VOC’s (Compostos Orgânicos Voláteis) que alcançam a superfície está numa concentração pequena ou inexistente. Além disso, as técnicas de medição de ²²²Rn estão bastante desenvolvidas. Os resultados obtidos demonstram que, similarmente a outros estudos, o gás 222Rn de solo apresenta um comportamento anômalo na área delimitada pela pluma de NAPL, sendo possível notar um déficit significativo na...
Keywords: Solos - Poluição; Radon; Hidrocarbonetos; Postos de serviços; Derramamento de óleo; Compostos orgânicos voláteis; Impacto ambiental; Rio Claro (SP)